Reverse electrochemical etching method for fabricating ultra-sharp platinum/iridium tips for combined scanning tunneling microscope/atomic force microscope based on a quartz tuning fork - Meza J.A.M. (2015)
We wish to thank Laurent Pham-Van (CEA/IRAMIS/SPEC/LEPO) for fruitful discussions on the tip etching process and Sylvain Foucquart (CEA/IRAMIS/NIMBE/LIONS) for his technical assistance. José Antonio Morán Meza would also like to acknowledge financial support from the Peru’s National Council of Science and Technology (Concytec), the Réseau Thématique de Recherche Avancée (RTRA-Triangle de la Physique), and the CEA/Direction des Relations Internationales (DRI).